Activation of ventrolateral preoptic neurons by the somnogen prostaglandin D(2) - Scammell, Thomas (The National Academy of Sciences, 1998)
Prostaglandin D(2) (PGD(2)) is an extensively studied sleep-promoting substance, but the neuroanatomical basis of PGD(2)-induced sleep is only partially understood. To determine potential regions involved in this response, we used Fos immunohistochemistry to identify neurons activated by infusion of PGD(2) into the subarachnoid space below the rostral basal forebrain. PGD(2) increased nonrapid eye movement sleep and induced striking expression of Fos in the ventrolateral preoptic area (VLPO), a cluster of neurons that may promote sleep by inhibiting the tuberomammillary nucleus, the source of the ascending histaminergic arousal system. Fos expression in the VLPO was positively correlated with the preceding amount of sleep and negatively correlated with Fos expression in the tuberomammillary nucleus. PGD(2) also increased Fos immunoreactivity in the basal leptomeninges and several regions implicated in autonomic regulation. These observations suggest that PGD(2) may induce sleep via leptomeningeal PGD(2) receptors with subsequent activation of the VLPO.